PENGARUH PENGGUNAAN BIOFLOK PADA LIMBAH AIR VERTIKULTUR TERHADAP KUALITAS LINGKUNGAN DAN PERTUMBUHAN SAYURAN HIDROPONIK - Haryani, Sri (AGRONIMAL: Jurnal Ilmiah Pertanian dan Peternakan, 2025)
The reuse of wastewater from plant cultivation is an important strategy in sustainable agriculture. Verticulture wastewater generally still contains nutrient residues that may pose environmental risks if not properly managed. Biofloc technology offers a biological solution through microbial activity capable of degrading organic compounds and dissolved nitrogen. This study aimed to analyze the effect of applying biofloc to verticulture wastewater on environmental quality and the growth of hydroponic vegetables. A completely randomized design was employed with three treatments: no biofloc (B0), low-dose biofloc (B1), and optimal-dose biofloc (B2), each replicated three times. Observed parameters included pH, ammonia, nitrate concentration, plant height, leaf number, and fresh biomass. The results indicated that the optimal biofloc treatment reduced ammonia levels by 35–40% and significantly improved plant growth and biomass production (p < 0.05). Plants under treatment B2 exhibited the highest growth and fresh weight. The application of biofloc effectively enhanced water quality while supporting vegetable productivity. This system shows strong potential as an environmentally friendly agricultural model and as an applied learning medium in vocational schools.